Does SME’s financing decisions follow pecking order pattern? The role of financial literacy, risk preference, and home bias in SME financing decisions - Henny Sulistianingsih; Fitri Santi (Cogent Business & Management)
This paper aims to explore the role of financial literacy, risk preference, and home bias in Minangkabau ethnic SME financing decisions, and whether their financing pattern follow the pecking order theory. The theoretical framework model was developed to determine the impact of financial literacy, risk preference, and home bias on the financing decisions of SMEs. The study applied the SEM-PLS method in testing the model. Data collection was carried out through online and offline survey techniques with a sample of 623 SMEs. The results reveal that home bias and risk preference have a negative direct effect on financing decision. Home bias also has a direct positive influence on risk preference. Financial literacy can minimize home bias from negative to positive toward financing decision. However, financial literacy does not have a direct effect on the financing decisions and does not have a significant direct influence on risk preference. Most SMEs have a low level of financial literacy, a high tendency for home bias and a high-risk preference. Financial literacy has strong positive moderation effect on the influence of home bias toward financing decision. Home bias make SME financing decision does not follow pecking order pattern. As SMEs financial literacy level is still very low, thus it is important for financial institutions to educate SMEs by providing several trainings about financial matters. The findings suggest to improve the financial literacy of SMEs informal association groups in order to help them reducing their home bias tendency. This study seeks to explore the pecking order pattern in financing decisions of SMEs.